Professional Ethics Based On Prophetic Pedagogy As The Foundation Of Teacher Professionalism Integrity - Rochim, Anita; Robandi, Babang (DAS CONFERENCE INTERNATIONAL SERIES, 2026)
This article, entitled "Professional Ethics Based on Prophetic Pedagogy as the Foundation of Teacher Professional Integrity," aims to critically analyze the position of professional ethics in teaching practice and its relevance to strengthening teachers' professional integrity amidst the increasingly technocratic and bureaucratic tendencies of professionalism. This study uses a qualitative approach with a critical literature study method, which regularly examines the latest literature related to professional ethics, teacher professionalism, and prophetic pedagogy as a conceptual framework for analysis. The results of the study indicate that professional ethics in teaching practice tends to be normative and reduced to an instrument of administrative compliance, thus potentially weakening the moral autonomy and reflective dimension of teachers as pedagogical subjects. The research discussion integrates these conceptual findings with a prophetic pedagogy framework that views professional ethics as a reflective moral praxis, as well as a critique of instrumental professionalism that ignores human values ​​and educational ethical responsibilities. Within this framework, teacher professional integrity is understood as the integrity of believed values, developed professional attitudes, and pedagogical actions manifested contextually in educational decision-making. The study's conclusions indicate that professional ethics based on prophetic pedagogy can serve as a conceptual foundation that strengthens teacher professional integrity in a comprehensive and meaningful manner. The impact of this research lies in its theoretical contribution to the development of studies on teacher professional ethics, as well as its practical implications for strengthening teacher professionalism, which is oriented not only toward technical competence but also toward ethical awareness and moral reflection in pedagogical practice.